Adverse effect of PNPLA3 p.I148M genetic variant on kidney function in middle‐aged individuals with metabolic dysfunction. Issue 10 (22nd March 2023) - Mantovani, Alessandro; Pelusi, Serena; Margarita, Sara; Malvestiti, Francesco; Dell'Alma, Michela; Bianco, Cristiana; Ronzoni, Luisa; Prati, Daniele; Targher, Giovanni; Valenti, Luca
Summary: Background: The PNPLA3 p.I148M variant is the main genetic determinant of nonalcoholic fatty liver disease, and PNPLA3 silencing is being evaluated to treat this liver condition. Data suggest that the p.I148M variant predisposes to kidney damage, but the relative contribution to kidney function, compared to overall genetic susceptibility, is not defined. Aims: We aimed to assess the effect of PNPLA3 p.I148M on the estimated glomerular filtration rate (eGFR) in individuals with metabolic dysfunction. Methods: We included 1144 middle‐aged individuals from the Liver‐Bible‐2022 cohort. Glomerular filtration rate (eGFR) was estimated using the Chronic Kidney Disease Epidemiology Collaboration equation. The effect of PNPLA3 p.I148M on eGFRCKD‐EPI levels was tested under additive genetic models adjusted for clinical predictors, ethnicity and a polygenic risk score of chronic kidney disease (PRS‐CKD). In a subset of 144 individuals, we examined the effect of PNPLA3 p.I148M on eGFRCKD‐EPI over a median follow‐up of 17 months. Results: The p.I148M variant was associated with lower eGFRCKD‐EPI levels (−1.24 mL/min/1.73 m 2 per allele, 95% CI: −2.32 to −0.17; p  = 0.023), independent of age, sex, height, waist circumference, systolic blood pressure, LDL‐cholesterol, transaminases, fasting insulin, albuminuria, lipid‐lowering drugs, ethnicity and PRS‐CKD score. In the prospective evaluation, the p.I148M variant was independently associated with faster eGFRCKD‐EPI decline (ΔeGFRCKD‐EPI −3.57 mL/min/1.73 m 2 per allele, 95% CI: −6.94 to −0.21; p  = 0.037). Conclusions: We found a detrimental impact of the PNPLA3 p.I148M variant on eGFRCKD‐EPI levels in middle‐aged individuals with metabolic dysfunction. This association was independent of established risk factors, ethnicity and genetic predisposition to CKD. PNPLA3 p.I148M silencing may protect against kidney damage progression in carriers. Abstract : The PNPLA3 p.I148M variant was associated with lower eGFR levels (an average loss of 1.24 mL/min/1.73 m2 of eGFR for each PNPLA3 risk allele), independent of established renal risk factors and potential confounders.